A randomized, placebo-controlled pilot trial of N-acetylcysteine on oxidative stress and endothelial function in HIV-infected older adults receiving antiretroviral treatment. (24th September 2016) - Gupta, Samir K.; Kamendulis, Lisa M.; Clauss, Matthias A.; Liu, Ziyue
Abstract : Supplemental Digital Content is available in the text